2021
DOI: 10.52547/ijhehp.9.3.246
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness web-based Educational Program on Optimal Use of Smartphones among Students with Nomophobia based on Self-Efficacy Theory: The Role of the Medical Librarian

Abstract: Background and Objective: Nomophobia is defined as the fear of being out of mobile phone contact and is considered a phobia of the modern age. The current study explored the effectiveness of the medical Librarian's web-based educational program on optimal use of smartphones among students with nomophobia based on self-efficacy theory. Materials and Methods: This semi-experimental study applied random controlled clinical trial and before-after Design groups with a follow-up method. The population included all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…The findings of this study showed that media literacy has an effect on the symptoms of nomophobia. This finding is in line with the study of Khosravi et al (2021) andDastghib Shirazi et al (2021). This finding can be explained in this way that Bandura, as the founder of the self-efficacy theory, believes that a person's assessment of his abilities in a specific situation has a strong influence on a person's decision-making in choosing an activity and insisting on it.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study showed that media literacy has an effect on the symptoms of nomophobia. This finding is in line with the study of Khosravi et al (2021) andDastghib Shirazi et al (2021). This finding can be explained in this way that Bandura, as the founder of the self-efficacy theory, believes that a person's assessment of his abilities in a specific situation has a strong influence on a person's decision-making in choosing an activity and insisting on it.…”
Section: Discussionsupporting
confidence: 92%
“…Media literacy training reduces information anxiety (Imanzadeh, Karimi, and Farajpour-Banab, 2019) and reduces the consequences of cyberspace addiction and nomophobia (Shirafken et al, 2020). In a study, Khosravi et al (2021) found that providing web-based health-oriented education by considering the audience's needs can positively affect reducing nomophobia in students. In the study of Dasghib Shirazi et al (2021), the existence of a relationship between media literacy and the phenomenon of mobile phone phobia was confirmed.…”
Section: Introductionmentioning
confidence: 99%